The crosstalk of intratumor bacteria and the tumor - Huang, Jiating; Mao, Yuqin; Wang, Lishun (Frontiers in Cellular and Infection Microbiology, 2024)
The in-depth studies reveal the interaction between the host and commensal microbiomes. Symbiotic bacteria influence in tumor initiation, progression, and response to treatment. Recently, intratumor bacteria have been a burgeoning research field. The tumor microenvironment is under vascular hyperplasia, aerobic glycolysis, hypoxia, and immunosuppression. It might be attractive for bacterial growth and proliferation. As a component of the tumor microenvironment, intratumor bacteria influence tumor growth and metastasis, as well as the efficacy of anti-tumor therapies. Therefore, understanding the intricate interplay of intratumoral bacteria and the host might contribute to better approaches to treat tumors. In this review, we summarize current evidence about roles of intratumor bacteria in tumor initiation and anti-tumor therapy, and what is remained to be solved in this field.